Estudio Contextual Del Ritual Nggua Y Su Relevancia Para La Escatología Católica De La Tribu Liti Pumbu, Manggarai Timur-NTT, Indonesia - Sanchez Boira, Anna; Abatan, Yofince; Jemali, Mikael (Pastoralia Jurnal Penelitian Dosen, 2025)
This study aims to examine the theological meaning of the nggua ceremony, a traditional death ritual practiced by the Liti Pumbu tribe in East Manggarai, and its relevance to Catholic eschatological teachings. Employing a qualitative-descriptive approach and ethnographic method, the research explores the local community’s understanding of life after death and the symbolic meanings embedded in the nggua ritual. Data were collected through participant observation, in-depth interviews, and documentation involving customary leaders and community members. The findings reveal that nggua is understood as a sacred transition of the soul toward eternal life and as an expression of communal faith in salvation and union with God and the ancestors. The ritual centers on pau (customary prayers) and the offering of sacrificial animals, symbolizing hope for heavenly peace and divine light. Although the community does not articulate the concept of eschatology in formal theological terms, they demonstrate a deep spiritual awareness of eternal life. Supporting factors for the preservation of this ritual include the transmission of ancestral values and strong spiritual convictions, while hindering factors involve the low engagement of younger generations and the influence of modernization. This study highlights the importance of inculturating the Catholic faith in local contexts and calls for pastoral and educational strategies that bridge the gap between doctrine and cultural expressions of belief.